Selection of patients with symptomatic vagal-induced sinus node dysfunction: Who will be the best candidate for cardioneuroablation? - Cai, Simin; Zheng, Lihui; Yao, Yan (Frontiers in Physiology, 2023)
Sinus node dysfunction is a multifaceted disorder with variable manifestations, the prevalence of which increases with age. In a specific group of patients, excessive vagal activity may be the sole cause. These patients are characterized as having recurrent daytime symptoms attributed to bradyarrhythmia, no evidence of organic sinus node lesions, cardiac vagal overactivation, and are non-elderly. For patients with sinus node dysfunction, permanent pacemaker implantation appears to be the ultimate solution, although it is not an etiological treatment. Cardioneuroablation is a promising emerging therapy that can fundamentally eliminate symptoms in a highly selective group of patients with sinus node dysfunction by denervation of the cardiac vagal nerve. Denervation with ablation for vagal-induced sinus node dysfunction can effectively improve sinus bradycardia and reduce syncope. To date, guidelines for selection of suitable candidates for cardioneuroablation remain lacking. The primary objective of this study is to distinguish the nature of abnormal sinus node function and to find methods for quantifying vagal tone. Clear selection criteria can help physicians to identify patients with autonomic imbalance, thereby maximizing patient’s benefits and increasing the success rate of cardioneuroablations.